YHWH is king : the development of divine kingship in ancient Israel - Flynn, Shawn W. (Vetus Testamentum, Supplements, 2014)
Amidst various methodologies for the comparative study of the Hebrew Bible, at times the opportunity arises to improve on a method recently introduced into the field. In YHWH is King , Flynn uses the anthropological method of cultural translation to study diachronic change in YHWH's kingship. Here, such change is compared to a similar Babylonian development to Marduk's kingship. Based on that comparison and informed by cultural translation, Flynn discovers that Judahite scribes suppressed the earlier YHWH warrior king and promoted a creator/universal king in order to combat the increasing threat of Neo-Assyrian imperialism. Flynn thus opens the possibility, that Judahite scribes engaged in a cultural translation of Marduk to YHWH, in order to respond to the mounting Neo-Assyrian presence.